Inductive & capacitive wireless power transfer system - Mazli, Mohamad Syafiq; Wan Fauzi, Wan Noor Nadira; Khan, Sheroz; Aznan, Khairil Azhar; Nataraj, Chandrasekharan; Adam, Ismail; Kadir, Kushairy; Ahmed, Musse Mohamud; Yaacob, Mashkuri (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
This paper studied the implementation of wireless power transfer through using a mix of inductive and capacitive coupling techniques to overcome the disadvantages of wired power transfer. The topology for the prototype of the combined system is based on LC-compensated topology, the combination of LCC-compensated topology of inductive power transfer together with LCLC-compensated of the capacitive power transfer. The power energy is transferred through the 30 mm x 30 mm of inductive coupler with the help of 61 mm x 61 mm of capacitive coupler. The simulation results proved that the power can be transferred through both inductive and capacitive coupler by observing the magnetic and electric fields. An experiment has proven that both inductive and capacitive coupler resonate together, using the compensation components in transferring power.